Compensation And Rewards In The Digital Age: The Development Of Performance Systems, Bonuses, And A Flexible Approach To Employee Rewards - Farika Nursasi; Karina Kemala Sari; William Janaldo; Noviarakhman Zagladi (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Purpose − In the rapidly evolving digital era, the paradigm of employee compensation and rewards is undergoing a fundamental transformation. The concept of Digital Compensation and Rewards has emerged as a response to these changes, emphasizing the development of adaptive performance systems, innovative bonus strategies, and flexible reward mechanisms. Overall, this paradigm introduces modern approaches to human resource management. As digitalization advances, compensation and reward systems are also undergoing significant changes, with the use of technology enabling the more efficient implementation of performance-based systems. Findings − The literature review indicates that technology has a significant positive impact on the employee recruitment process. Additionally, the implementation of digital compensation and rewards plays a crucial role in enhancing employee performance. Design/Methodology/Approach − By utilizing data-driven performance assessments through digital platforms, companies can collect and analyze employee performance data in greater detail. This enables more objective and accurate evaluations, while also creating opportunities to provide appropriate recognition for individual contributions. Practical Implications − These include improving recruitment processes through digital technology and social media, adapting compensation systems to incorporate digital performance bonuses and application-based incentives, providing flexibility in rewards tailored to individual preferences, leveraging data analytics to accurately measure employee performance, and developing HR competencies in integrating digital technology into human resource management. By addressing these implications, organizations can strengthen their HR strategies to navigate the challenges and opportunities of the digital era, ultimately supporting organizational growth and success. Originality/Value − This study offers an innovative perspective on how organizations can leverage digital technology and more flexible bonus systems to enhance employee motivation and productivity. With a focus on the digital era, it highlights the importance of adapting to technological changes in human resource management. The key value of this paper lies in providing practical guidance for organizations aiming to optimize employee performance and reward systems in an increasingly dynamic digital environment.